Statistical analysis of mathematical marks in secondary schools and university - Čirba, Stasys; Daunoravičius, Jonas; Raulynaitis, Juozas (Lietuvos matematikos rinkinys, 2004)
In this article statistical analysis and influence of marks of mathematics in middle school to marks in winter session is described. The findings of the investigation indicates that the results of the University first session examination in mathematics depend on what level a pupil took the examination before entering the University. Namely, the results are essentially influenced by factor whether a pupil took the examination at a state examination center or at school.
Keywords: statistical anlysis; secondary school; egzamination